2023
DOI: 10.7759/cureus.40682
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of COVID-19 on Preterm Birth Among Pregnant Women in Al-Qassim, Saudi Arabia

Lama S Alhumaidan,
Nadiah Alhabardi,
Sarah S Aldharman
et al.

Abstract: Background: Pregnant women are regarded as a unique group due to the distinct immunological condition that pregnancy produces, which makes pregnant women more susceptible to respiratory infections like coronavirus disease 2019 (COVID-19) and its consequences. During pregnancy, many viral infections have been recognized to increase the risk of adverse obstetrical outcomes such as preterm delivery. The purpose of this study was to investigate the effects of COVID-19 infection on preterm birth in pregnant women i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Pregnant women with COVID-19 have been found to have an increased risk of severe illness and adverse pregnancy outcomes compared to their non-pregnant counterparts [ 7 , 8 ]. These outcomes prominently include preterm birth, a significant concern given its implications for neonatal health [ 9 , 10 ]. Studies have shown that a COVID-19 infection during pregnancy increases the risk of preterm birth by up to 50% higher than the non-infected counterparts [ 11 ], necessitating a deeper understanding of its pathophysiology, implications, and risk factors [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Pregnant women with COVID-19 have been found to have an increased risk of severe illness and adverse pregnancy outcomes compared to their non-pregnant counterparts [ 7 , 8 ]. These outcomes prominently include preterm birth, a significant concern given its implications for neonatal health [ 9 , 10 ]. Studies have shown that a COVID-19 infection during pregnancy increases the risk of preterm birth by up to 50% higher than the non-infected counterparts [ 11 ], necessitating a deeper understanding of its pathophysiology, implications, and risk factors [ 12 ].…”
Section: Introductionmentioning
confidence: 99%